Performance Evaluation of Enhanced Oil Recovery by Host–Guest Interaction of β-Cyclodextrin Polymer/Hydrophobically Associative Polymer - Xi Li; Zhongbing Ye; Pingya Luo (Molecules)
In this work, a hydrophobically associative polymer (HAP) was mixed with β-cyclodextrin and epichlorohydrin polycondensate (β-CDP) in an aqueous solution to enhance the intermolecular interaction through host–guest inclusion between hydrophobes and cyclodextrins. Results showed that the host–guest interaction improved the thickening ability and viscoelasticity of the HAP solution and maintained its shear thinning behavior. The host–guest inclusion system demonstrated special viscosity–temperature curves and variable activation energy. Enhanced oil recovery (EOR) performance tests showed that the oil increment produced by the host–guest inclusion system was 5.5% and 9.3% higher than that produced by the HAP and the partially hydrolyzed polyacrylamide solution, respectively. Compared with pure HAP, β-CDP/HAP has a better comprehensive performance and is more attractive for EOR in high-temperature reservoirs.